2014
DOI: 10.4103/0259-1162.128905
|View full text |Cite
|
Sign up to set email alerts
|

Airway management: A comparative study in cleft lip and palate repair surgery in children

Abstract: Background:Cleft lip with or without palate is one of the common congenital malformations.Aim:To evaluate the per-operative complications of anesthesia, a comparative study was conducted in children using the endotracheal tubes available in the Institute so that the complications can be averted in future procedures.Materials and Methods:The rural population of Tripura, India.Result:Awareness was generated and the incidence of repair surgeries of cleft lip and palate was thus increased considerably in Dr. B. R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…Frequency (4.3%) of respiratory tract infections in our study was similar to that by [ 9 ], who found upper respiratory tract infections in 3.8% of the children with CL/Ps. Our result, however, was higher than that by [ 10 ] (2.7%) but lower than those by [ 29 ] (11.1%) and [ 31 ] (26%). The differences between studies may be due to under- or overestimation of respiratory infections; the diagnosis in our study was purely clinical.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Frequency (4.3%) of respiratory tract infections in our study was similar to that by [ 9 ], who found upper respiratory tract infections in 3.8% of the children with CL/Ps. Our result, however, was higher than that by [ 10 ] (2.7%) but lower than those by [ 29 ] (11.1%) and [ 31 ] (26%). The differences between studies may be due to under- or overestimation of respiratory infections; the diagnosis in our study was purely clinical.…”
Section: Discussioncontrasting
confidence: 90%
“…Malnutrition was the third most common medical condition, with a frequency of 7.5%, higher than that reported in other studies in developing countries: [ 9 ] reported 2.8% in Nigeria, [ 10 ] reported 3.6%, and [ 29 ] reported 3.9% in India. As stated above, children with CL/Ps have feeding difficulties, which can lead to malnutrition.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Regarding the choice of endotracheal tube (TET), there is no single criterion; the use of RAE (Ring-Adair-Elwyn) U-shaped tubes is recommended for lip surgery and reinforced tubes also known as spiral-shaped spiral wire reinforcement inside and along the tube wall to reduce your occlusion during palate surgery. Other frequently reported are Oxford or "L"-shaped tubes to avoid couplings [24,25].…”
Section: Endotracheal Intubationmentioning
confidence: 99%